Sosialisasi Organisasi dan Manajemen Usaha untuk Meningkatkan Literasi Keuangan Masyarakat Desa Gantar - Supriadi, Supriadi M; Sahid, Umar; Dzulfa Fadilah, Azzahra; Putri Hanifah, Hasna; Asih Nusantari, Dewi; Sobirin (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The community service activity titled Socialization of Business Organization and Management to Improve Financial Literacy in Gantar Village was carried out to strengthen the economic capacity of rural communities by enhancing managerial and financial literacy skills. This initiative was motivated by the limited financial record-keeping practices and unstructured business management among micro-entrepreneurs in Blok Babakan Betawi, Gantar Village. The program employed a qualitative-descriptive design through a participatory approach, involving 28 participants from various business backgrounds. The activities consisted of delivering materials on the Five Pillars of Business, conducting financial management training, interactive discussions, and reflective evaluations. The results indicated a significant improvement in participants’ understanding of structured business management, financial recording, and strategies for developing sustainable business networks. Participants also demonstrated a more positive attitude toward organized and data-based business practices. Moreover, this activity fostered social impacts by cultivating collective awareness of collaboration and continuous learning within local entrepreneurship. Therefore, this training serves as an essential step toward strengthening a self-reliant and adaptive local economy in the digital era.